Male display characters, gonadal maturation and androgens in the cichlid fish Oreochromis mossambicus - Oliveira, Rui Filipe (2012)
The relationships between gonadal maturation and the expression of behavioral and morphological display characters in O. mossambicus was investigated and the possible role of androgens in the coordination of this process was evaluated using genital papilla size as a bioassay for androgen levels. Morphological and behavioral displaying characters were found to be correlated among themselves. The sexually dimorphic characters were correlated with gonad maturation and androgen levels, but not with the gonado-somatic index. Gonad maturation and androgen levels were closely related. Territoriality and other behavioral variables involved in reproduction were also correlated with gonad maturation and androgen levels. These data suggest that in O. mossambicus androgens play a mediating role between gonadal maturation and the expression of display characters, both morphological and behavioral.